Pengaruh Literasi Keuangan Syariah terhadap Minat Investasi pada Pasar Modal Syariah - Dini Selasi; Siska Nurpitasari; Meli Saputri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study focuses on analyzing the impact of Islamic financial literacy on the interest in investing in the Shariamarket. Islamic financial literacy involves a deep understanding of financial principles that comply with Islamic law, including zakat, riba, and the principle of justice in financial transactions. The growing awareness of halal and Sharia-compliant investments suggests that Islamic financial literacy can be a decisive factor in investment decisions. This study uses a quantitative method by distributing questionnaires to 200 respondents, comprising prospective investors and active investors in the Sharia capital market. The results of the study indicate that higher levels of Islamic financial literacy positively correlate with greater interest in investing in Sharia capital market instruments such as sukuk and Sharia mutual funds. These findings highlight the need for more intensive Islamic financial education programs to improve public literacy and support the development of the Sharia capital market in Indonesia. Supporting policies and innovations in Sharia investment products are also identified as crucial factors in encouraging investment interest. Thus, this study concludes that enhancing Islamic financial literacy can play a significant role in advancing the Sharia capital market and supporting a more inclusive Islamic economy. This research demonstrates that Islamic financial literacy significantly influences investment interest in the Sharia capital market. Investors with a solid understanding of Islamic financial principles such as riba (usury), zakat (almsgiving), and profit-sharing are more likely to opt for Sharia-compliant investment products like sukuk (Islamic bonds) and Sharia mutual funds. The study underscores the importance of comprehensive financial education programs and the availability of accessible information to enhance Islamic financial literacy among the public. These efforts are expected to increase participation in the Sharia capital market and support more inclusive and sustainable economic growth in Indonesia.